Upaya Guru PAI dalam Menanamkan Nilai-nilai Akhlak Melalui Budaya Sekolah - Ahsin, Muhammad; Inayatul Ilahiyah, Iva (ILJ: Islamic Learning Journal, 2025)
The purpose of this article is to describe the efforts of PAI teachers in instilling moral values through school culture at Nur Muhammad Wonoayu Junior High School in Mojoagung Jombang. The research method used is a qualitative approach with a case study type of research. Data collection techniques were carried out using observation, interviews, documentation, source triangulation analysis techniques. The results showed that: 1) PAI teachers have an important role in instilling moral values to students to form noble characters. Through the exemplary approach, teaching the value of piety, mutual respect, helping, and protecting the environment is effectively instilled. Activities such as practicing religious teachings, community service, and habituation of manners are the main methods in creating students who are noble, caring for others, and responsible. 2) The school builds a school culture based on three main values: honesty, cooperation and healthy competition. Honesty is applied in learning and school policies. Cooperation is developed through group and extracurricular activities, while healthy competition encourages sportsmanship and respect for others' efforts. These three values shape students into honest, responsible and challenge-ready individuals. 3) Teachers play an important role in instilling moral values through exemplary teaching, and habituation of moral values such as devotion, mutual respect and responsibility. school culture that emphasizes honesty, cooperation and healthy competition.